Inhibition of potato tuber sprouting by pressure treatments - Saraiva, Jorge A.
In this study, we found that pressure treatments of 100 MPa applied for 5 and 10 min inhibited the sprouting of potato tubers that were stored for 3 months before the pressure treatments, for at least 6 weeks at 18 C. Less intense pressure treatments of 30 and 50 MPa for 5 and 10 min did not inhibit sprouting, but hindered sprout development, evaluated by sprout length, elongation rate and mass. Pressure treatments caused a higher inhibition of sprouting, when applied to tubers after 5 months of storage, before the application of the pressure treatments. For these tubers, pressure treatments at 50 and 100 MPa for 5 and 10 min inhibited sprouting for at least 6 weeks at 18 C. For the same tubers, a pressure treatment at 30 MPa for 10 min already showed some inhibitory eﬀect on sprouting and hindered sprout development. Pressure treatments show great potential to be used, as a nonthermal and chemical-free method, to control sprouting of potato tubers.